Culturally Responsive Teaching: A Framework for Educating Diverse Audiences - John Diaz; Cecilia Suarez; Laura Valencia (EDIS)
As the diversity of Extension clientele continues to grow, it is important for Extension educators to consider new ways of supporting this population. The purpose of this new 5-page article is to provide a framework for educating diverse audiences to assist in helping these audiences attain the learning outcomes of Extension education programs. This includes: (1) acquiring a knowledge base of diverse cultures, (2) designing or utilizing culturally relevant curricula, (3) utilizing cultural caring and developing a learning community, (4) practicing intercultural communications, and (5) establishing cultural congruity in classroom instruction. Written by John Diaz, Cecilia Suarez, and Laura Valencia and published by the UF/IFAS Department of Agricultural Education and Communication. https://edis.ifas.ufl.edu/wc341